High-sensitivity troponins in dialysis patients: variation and prognostic value - Snaedal, Sunna (Clin Kidney J, 2020)
BACKGROUND: Dialysis patients have a high prevalence of cardiovascular mortality but also elevated cardiac troponins (cTns) even without signs of cardiac ischaemia. The study aims to assess variation and prognostic value of high-sensitivity cTnI and cTnT in prevalent dialysis patients. METHODS: In 198 prevalent haemodialysis (HD) and 78 peritoneal dialysis (PD) patients, 4-monthly serum troponin I and T measurements were obtained. Reference change values (RCVs) were used for variability assessment and competing-risk regression models for survival analyses; maximal follow-up was 50 months. RESULTS: HD and PD patients had similar troponin levels [median (interquartile range) troponin I: 25 ng/L (14–43) versus 21 ng/L (11–37), troponin T: 70 ng/L (44–129) versus 67 ng/L (43–123)]. Of troponin I and T levels, 42% versus 98% were above the decision level of myocardial infarction. RCVs were +68/−41% (troponin I) and +29/−23% (troponin T). Increased variability of troponins related to higher age, male sex, protein-energy wasting and congestive heart failure, but not ischaemic heart disease or dialysis form. Elevated troponin T, but not troponin I, predicted death after adjusting for confounders. CONCLUSIONS: A large proportion of prevalent dialysis patients without current established or ongoing cardiac events have elevated levels of high-sensitivity cTns. Mortality risk was doubled in patients with persistently high troponin T levels. The large intraindividual variation of cTns suggests that serial measurements and reference change levels may be used to improve diagnostic utility. However, evidence-based recommendations require more data from large studies of dialysis patients with cardiac events.